Effect of foliar application of low molecular weight chitosan on rice growth and yield in the Sudan Savanna Zone of Ghana - Jacqueline Onumah; Peter Osei Boamah; Wilberforce Orlando Aduguba; Benjamin Apam; Joshua Kwadwo Gmantrim (Carbohydrate Polymer Technologies and Applications)
Rice is a crucial staple crop in many parts of the world, including Ghana. The Upper East Region, known for its agricultural activities, faces challenges in optimizing rice yields due to factors such as soil fertility, pest infestations and varying climatic conditions. While foliar applications of different substances have been extensively studied, there is limited research on the effects of low-molecular-weight chitosan (LMWCHT) on rice growth and yield. Chitosan, a biopolymer derived from chitin, has shown potential in enhancing plant growth and resistance to pests and diseases. However, the optimal concentrations and timing of application for maximum effectiveness on AGRA rice (Bansi) remain unclear. Given the critical importance of rice as a food source and the need to improve agricultural sustainability, this study aims to evaluate the effects of LMWCHT on rice growth and yield over two consecutive harvests. The study utilized a Randomized Complete Block Design (RCBD) with LMWCHT concentrations of 50, 75, 100, and 125 mg/L. The application of LMWCHT had a significant effect on dry straw weight. From the study, 100 mg/L LMWCHT produced the highest rice yield. The findings suggest that LMWCHT can greatly improve rice yields and promote sustainability in regions experiencing similar agricultural challenges.